KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Purba, Aminatul Juhri; Amiruddin, Amiruddin; Siregar, Astri Novia (Hijri, 2023)
The aim of this research is to determine the leadership applied by the school principal to improve the performance of teachers at SMP Negeri 1 Sipispis so that they work more effectively and efficiently. The method used in the research is a descriptive approach with qualitative analysis, namely by using data collection techniques in the field through the process of interviews, observation and documentation. The research results show the principal's leadership in improving teacher performance at SMP Negeri 1 Sipispis with strategies, namely: Teacher task distribution meetings, directing teachers to create lesson plans, increasing teacher capacity through the MGMP program, monitoring and evaluating teacher performance. It is hoped that the participant leadership pattern implemented by the school principal will be able to improve teacher performance at SMP Negeri 1 Sipispis. Obstacles in improving teacher performance include the short term of principalship, the lack of discipline of some teachers due to the long distance from home to school, and the small income or honorarium received by teachers.Keywords:Principal Leadership, Teacher Performance